Optimization of the scale-up production process for high-yield laccase from white-rot fungi - Ma, Yaping; Liu, Minchang; Gu, Ruifang; Zhang, Rongya; Ji, Xiaomei; Zhang, Juan; Wen, Wu; Peng, Zheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionLaccase exhibits significant applications in food additives, wastewater treatment, and biomass processing. Fungal laccase exhibits high activity, good stability, and excellent performance. However, scale-up production of high-yield laccase from fungi is challenging. This study aimed to identify crucial factors affecting enzyme production and analyze the enzymatic properties of laccase during fermentation.MethodsA laccase-producing white-rot fungus was used for fermentation process optimization in 200 L and 1200 L fermenters. The Plackett–Burman design revealed three significant influencing factors: temperature, aeration ratio, and agitation speed. The steepest ascent experiment was used to approximate the maximum response region, followed by the establishment of a regression model between experimental factors and laccase activity using the Box–Behnken response surface methodology and optimal fermentation condition selection.ResultsThe optimal conditions for laccase production by Ganoderma lucidum fermentation were 30°C temperature, 0.66 aeration ratio, and 100 rpm agitation speed, achieving a maximum laccase activity of 214,185.2 U/L. Dissolved oxygen (DO) was a crucial factor for high laccase yield, and its maintenance at a high level in the fermentation system significantly enhanced the enzyme activity. Fermentation batches with varying laccase production levels exhibited a trend of decreasing pH and a subsequent increase in the mid-to-late fermentation stages. With decreased pH, the DO level started declining; when DO stabilized, the pH started to rebound, coinciding with the peak laccase activity, indicating a signal of fermentation endpoint in industrial production.DiscussionThis study provides valuable theoretical and data support for the industrial production of laccase by fungi through optimized fermentation processes.